AI FEEDBACK VS. HUMAN FEEDBACK IN WRITTEN AND SPOKEN EXERCISES - To‘lqinova Mushtariybegim Erkinjon qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article explores the differences between AI feedback and human feedback in written and spoken exercises, focusing on their impact on learner development. While AI provides instant, consistent, and objective response, human feedback offers emotional support along with contextual understanding and motivation. The research highlights the strengths and limitations of each approach, emphasizing the need for a balanced integration. A humanistic perspective is adopted to value empathy, encouragement, and personalized learning in language education.